Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1126/science.287.5456.1253
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Experimental Liver Cirrhosis in Mice by Telomerase Gene Delivery

Abstract: Accelerated telomere loss has been proposed to be a factor leading to end-stage organ failure in chronic diseases of high cellular turnover such as liver cirrhosis. To test this hypothesis directly, telomerase-deficient mice, null for the essential telomerase RNA (mTR) gene, were subjected to genetic, surgical, and chemical ablation of the liver. Telomere dysfunction was associated with defects in liver regeneration and accelerated the development of liver cirrhosis in response to chronic liver injury. Adenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
287
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 379 publications
(308 citation statements)
references
References 48 publications
15
287
0
1
Order By: Relevance
“…Telomerase gene delivery inhibited experimental liver fibrosis in mice,36 and an increased incidence of germline telomerase mutations was detected in patients with cirrhosis compared to noncirrhosis controls, suggesting that telomere shortening can accelerate cirrhosis formation 37, 38. It was postulated that somatic TERT promoter mutations could counterbalance germline loss‐of‐function mutations in pulmonary fibrosis 39.…”
Section: Discussionmentioning
confidence: 99%
“…Telomerase gene delivery inhibited experimental liver fibrosis in mice,36 and an increased incidence of germline telomerase mutations was detected in patients with cirrhosis compared to noncirrhosis controls, suggesting that telomere shortening can accelerate cirrhosis formation 37, 38. It was postulated that somatic TERT promoter mutations could counterbalance germline loss‐of‐function mutations in pulmonary fibrosis 39.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that knockout mice lacking telomerase activity have reduced regeneration capacity indicates however that telomerase activity can contribute to liver regeneration. 9 Recent reports indicated that expression of TERT can also exert some telomere independent effects that could be important for regulation of tissue regeneration in response to injury. It was shown the TERT acts as a co-factor controlling transcriptional regulation of Wnt target genes in mice.…”
Section: Introductionmentioning
confidence: 99%
“…This concept is supported by studies demonstrating that the telomeres of chronically diseased human livers are shorter than those of age-matched controls [9][10][11] Although relatively little work has been done examining the effects of liver injury on telomeres in experimental animals, the available data are intriguing. For example, mice with a targeted deletion of one of the components of telomerase demonstrate impaired hepatic regeneration and accelerated fibrogenesis in the context of liver injury [12]. Consistent with those findings, the livers of rats chronically treated with CCl 4 have been reported to show extensive telomere shortening, while both CCl 4 -induced fibrosis and telomere shortening were attenuated in rats concurrently treated with estrogen, which enhances telomerase expression [13].…”
Section: Introductionmentioning
confidence: 68%
“…Given that telomere shortening and/or impaired telomerase activity have been linked to the development of progressive fibrosis in chronic liver injury [9][10][11][12], it is likely that enhanced telomerase activity serves a protective function. One means by which telomerase may confer protection during chronic liver injury is through the prevention of telomere shortening with its resultant replicative arrest and senescence.…”
Section: Discussionmentioning
confidence: 99%